EKSPLORASI TERUMBU KARANG PULAU PISANG DI PANTAI AIR MANIS PADANG - Nina Ismayani; Risa Aprina; Feni Maria; Imeria Waruwu; Jarius Sagalak (Jurnal Azimut, 2025)
Coral reefs are marine ecosystems that play an important role in maintaining ecological balance and providing economic benefits for coastal communities. Indonesia, as an archipelagic country, possesses extensive coral reef resources, including those in West Sumatra. This study aims to examine the condition of the coral reef ecosystem on Pisang Island, Air Manis Beach, Padang, as well as the efforts for its preservation and management. The method used was descriptive qualitative with data collection techniques through direct observation in April 2025. The observation results showed that the coral reef ecosystem in the area was relatively well preserved and located in shallow waters. Conservation efforts were carried out through coral transplantation education and the utilization of technology such as bioreeftek. Sustainable management, along with awareness among local communities and tourists, are important factors in coral reef conservation. This study emphasizes that the involvement of various stakeholders, including legal regulations, environmental education, and technological innovation, is crucial in maintaining the sustainability of coral reef ecosystems in Indonesia.